Corrosion Resistance and Nano-Mechanical Properties of a Superhydrophobic Surface - Chun-Wei Yao; Ian Lian; Jiang Zhou; Paul Bernazzani; Mien Jao; Md Ashraful Hoque (Lubricants)
Nanoindentation has been used to characterize the mechanical and creep properties of various materials. However, research on the viscoelastic and creep properties of superhydrophobic surfaces remains limited. In this study, a superhydrophobic coating was developed and its corrosion resistance was evaluated initially. Electrochemical impedance spectroscopy (EIS) results quantitatively confirm the enhanced anti-corrosion performance of the superhydrophobic coating. Subsequently, this study investigates the creep, hardness, strain rate sensitivity, and viscoelastic behavior of the superhydrophobic surface at the nanoscale before and after accelerated corrosion exposure. Our findings reveal that during the creep tests, the logarithmic values of creep strain rate and stress exhibited a good linear relationship. Additionally, the surface retains its key viscoelastic properties (hardness, storage modulus, loss modulus, and tan δ) even after exposure to corrosion. These results highlight the surface’s robustness under corrosive conditions, a crucial factor for applications requiring both mechanical integrity and environmental resilience.